Factors Related to the Achievement of the Target of the Maternal and Child Health Program at the Konawe District Health Center - Djafar, Samrudin; Sunarsih, Sunarsih; Tasnim, Tasnim; Hariadhin Depu, Anry (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: Based on the Konawe District Health Profile, it is known that in general the trend of delivery assistance coverage by health workers is known to be 91.20% in 2014, in 2015 there was no increase, namely 91.20%, for 2016 it decreased to 72.80%, for 2017 also increased to 75.70% but in 2018 it decreased drastically to 61.10%. Method: This type of research is quantitative using a cross-sectional design, the research was conducted at the Konawe district health center, with a population of 29 health centers and a sample of 27 health centers and there were 5 people representing 1 health center so that the total sample of the study was 135 respondents. Result: It is known from the results of data analysis and obtained the value of X2Count or Chi- Square 66,849 > from 3.841 or X2table and a Phi value of 0.587 which means it has a moderate relationship between ability and the achievement of the MCH program. It is known from the results of data analysis and obtained the value of X2Count or Chi-Square 72.824 > from 3,841 or X2table and the value of Phi 0.603 which means it has a strong relationship between motivation and the achievement of the MCH program. Conclusion: There is a moderate relationship between the ability of health workers and the Maternal Health Program and a strong relationship between the motivation of health workers and the Maternal and Child Health Program.